Bidirectional association between functional disability and multimorbidity among middle-aged and older adults in Thailand - Pengpid, Supa; Peltzer, Karl; Anantanasuwong, Dararatt (Frontiers in Public Health, 2022)
Background: The purpose of this study was to assess the bidirectional association between multimorbidity (MM) and functional disability among middle-aged and older adults in a longitudinal study in Thailand. Methods: We analyzed longitudinal data of participants 45 years and older from two consecutive waves (in 2015 and 2017) of Health, Aging and Retirement in Thailand (HART). Functional disability was assessed with a 4-item daily living activity scale. Logistic regression analysis was conducted to assess the association between baseline functional disability and incident multimorbidity (MM, ≥2), and baseline morbidity and incident functional disability. Results: The results indicate that in total, 1716 without morbidity at baseline and 3529 without functional disability at baseline were included. At follow-up 16.7% and 20.0% of functional disability cases and 7.1% and 3.6% of nonfunctional disability cases developed 2 morbidities and 3 or more morbidities, respectively, and at follow-up 6.6% of MM cases and 4.0% of non-MM cases developed functional disability. In the final logistic regression model, adjusted for education, income, age, marital status, sex, smoking tobacco, body mass index, alcohol use, physical activity, and social engagement, functional disability at baseline was positively associated with incident MM (≥2) (aOR: 2.58, 95% CI: 1.42 to 4.72), and MM (≥3) at baseline was positively associated with incident functional disability (aOR: 1.97, 95% CI: 1.13 to 3.43). Conclusions: MM and functional disability were bidirectionally associated.